2016
DOI: 10.1007/s11307-016-0986-1
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal Imaging Reveals Improvement of Blood Supply to an Artificial Cell Transplant Site Induced by Bioluminescent Mesenchymal Stem Cells

Abstract: PurposeAn artificial site for cell or pancreatic islet transplantation can be created using a polymeric scaffold, even though it suffers subcutaneously from improper vascularisation. A sufficient blood supply is crucial for graft survival and function and can be enhanced by transplantation of mesenchymal stem cells (MSCs). The purpose of this study was to assess the effect of syngeneic MSCs on neoangiogenesis and cell engraftment in an artificial site by multimodal imaging.ProceduresMSCs expressing a gene for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 41 publications
(45 reference statements)
2
13
0
2
Order By: Relevance
“…Because subcutaneous vascularisation is insufficient for islets, several approaches have been advanced with the aim of improving neoangiogenesis, such as the incorporation of vascular endothelial and fibroblast growth factors [ 17 ] and mesenchymal stem cells (MSCs) [ 10 , 18 ]. Our previous studies have also confirmed the improvement of blood supply in scaffolds induced by MSCs [ 15 , 19 ]. In other models, cotransplantation of pancreatic islets in conjunction with MSCs have resulted in improved graft revascularisation, graft survival, and better transplantation outcomes [ 20 , 21 ].…”
Section: Introductionsupporting
confidence: 72%
See 2 more Smart Citations
“…Because subcutaneous vascularisation is insufficient for islets, several approaches have been advanced with the aim of improving neoangiogenesis, such as the incorporation of vascular endothelial and fibroblast growth factors [ 17 ] and mesenchymal stem cells (MSCs) [ 10 , 18 ]. Our previous studies have also confirmed the improvement of blood supply in scaffolds induced by MSCs [ 15 , 19 ]. In other models, cotransplantation of pancreatic islets in conjunction with MSCs have resulted in improved graft revascularisation, graft survival, and better transplantation outcomes [ 20 , 21 ].…”
Section: Introductionsupporting
confidence: 72%
“…Microvascular density (MVD) assessment was performed on four serial sections from each scaffold. MVD was evaluated as the number of CD31-positive microvessels counted at a magnification of ×400 as previously described [ 19 ]. The results were expressed as the mean microvessel count with standard deviation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Porém, esse resultado não foi devido à quantidade utilizada, pois a quantidade de células-tronco diferenciadas ou não (5x10 5 células por animal), aplicadas na lesão se assemelhou a outro estudo (GÁLISOVÁ et al, 2017), e foi efetiva uma vez que se observou diferenças, como melhora funcional e no local da lesão naqueles animais que as receberam.…”
Section: Estudo 3-"teste In Vivounclassified
“…Observou-se que ao terceiro dia foi quando mais se adquiriu melhores avaliações da bioluminescência, que foi decaindo com o passar do tempo (GÁLISOVÁ et al, 2017). No presente estudo o tratamento com ADSC-CC D7 resultou em redução do processo degenerativo dos axônios, o que indicou mais uma funcionalidade in vivo das ASDC além da relatada anteriormente.…”
Section: Estudo 3-"teste In Vivounclassified